Internationalization of the Curriculum and the “New Normal’: An Australian Perspective - Whitsed, Craig; Green, Wendy (International Higher Education, 2015)
Globalization, as a disruptive force, challenges us to reconsider enduring assumptions that frame conceptualizations of internationalization in the Australian higher education context and internationalization of the curriculum more broadly. Drawing on the perspectives of Fazal Rizvi, we problematize the new normal and argue that, if the transformative potential of curriculum internationalization is to be realized, assumptions about what is considered normal need to be challenged. To accomplish this, individual faculty (academics), their disciplines, and their institutions need to engage in critically reflective new imaginings of the transformative possibilities and the rich potential the new normal affords, and respond reflexively with open minds.